Yaqin, Amina. Gender, Sexuality and Feminism in Pakistani Urdu Writing. ISBN 9781785277566 (Anthem Press, 2022), 280 pages - Langah, Nukhbah Taj (SARE: Southeast Asian Review of English, 2024)
This book review focuses on Amina Yaqin, Gender, Sexuality and Feminism in Pakistani Urdu Writing (Anthem Press, 2022). The book is a rare contribution to feminist studies in the South Asian context and offers a new perspective to feminist scholars. The book defies over-reliance on Western feminist theories to argue that the convoluted social and political context of South Asia demands a nuanced understanding and reframing of the theoretical frameworks.